Aerosol assisted atmopheric pressure PE-CVD of drug containing nano-capsules. (7th November 2019) - Lo Porto, C.; Palumbo, F.; Treglia, A.; Camporeale, G.; Favia, P.
Abstract: In this review an overview is given on bio-composite coatings, on their applications and the plasma-based processes for their deposition. In particular, we describe the innovative possibility to deposit, via aerosol-assisted atmospheric pressure plasma, drug containing nano-capsules in a one-step process. The application of these peculiar bio-composite materials as cyto-compatible bactericidal drug release coatings have been examined, with different molecules embedded in the same polyethylene-like plasma-deposited matrix: vancomycin, gentamicin and lysozyme. In conclusion, a hypothesis on the formation mechanisms of the nano-capsules is proposed, which could be very interesting for numerous potential applications.